Hybrid effectiveness-implementation study designs in sports injury prevention research - Hayley J. Root; Monica R. Lininger; Lindsay J. DiStefano (Frontiers Media S.A., 2022)
Despite vast evidence supporting the effectiveness of lower extremity injury prevention programs in a variety of sport settings, age groups, and levels of competition, there is limited evidence on implementation strategies that positively impact the feasibility, scale-up and sustainability of such programs. Sport-related injury prevention is affected by the research-to-practice gap, a pervasive issue in healthcare, where high-quality experimental research is not used in routine clinical practice. An intervention shown to be efficacious in a controlled environment, such as a lab or in a field-study conducted by scientists, will demonstrate a decline in benefit when implemented in the intended clinical setting. Real-world considerations, such as foundational knowledge and training, time constraints, or end user motivation, influence the quality and consistency of implementation. Acknowledging and addressing implementation barriers in a systematic way is essential to promote effective program dissemination. Study design methods that measure both clinical effectiveness and implementation strategies need to be identified. Hybrid effectiveness-implementation designs simultaneously measure both an intervention's effect on clinical outcomes as well as critical information related to implementation strategy; however these study designs are not frequently utilized. The purpose of this mini-review is to describe: the basics of hybrid designs, rationale for using hybrid designs, and examples of how these designs could be used in athletic healthcare injury prevention research.